Reasons for the lack of sports performance of Comercial F.C. - Ferraresi de Araujo, Gerado José; Costa, André Lucirton; Carvalho, Cesar Machado (Revista de Administração da UFSM, 2012)
The international football, according to the report of the Plan for Modernization of the Brazilian Football FGV (2000) annual turnover of approximately 250 billion, while Brazil represents only 1% of the total. The Commercial F. C. headquartered in the city of Ribeirão Preto (SP), had its poly auctioned sports stadium partially forbidden for 23 years and not disputed the series A1, A3series being relegated to the Campeonato Paulista in 2009. This study aimed to identify those factors that hinder sports performance of the Commercial F. C., to do so, we studied its history, its relations with the government and legislation, market performance, partnerships established, administrative structures and results in the tournaments played between 2007 and 2008 to discuss their management problems. The methods used were research-explanatory and qualitative semi-structured interview to build a case study. We conclude that the gap between the formal structure and practice of members of the answers as a key element in the absence of the club’s sports performance.